Early Neonatal Outcomes in Premature Rupture of Membranes Beyond Twenty-eight Weeks of Gestation in a Tertiary Care Hospital of Coastal Karnataka - Sweta Shanbhag; Rashmi Alva (Galenos Yayinevi, 2020)
Aim:Premature rupture of membranes (PROM) is a significant risk factor for various adverse neonatal outcomes such as prematurity, respiratory distress, birth asphyxia and early onset neonatal sepsis. Due to the public health relevance of this topic and its higher burden on health care services, this study was carried out to the identify risk factors and predictors of neonatal outcomes among babies born to mothers with PROM.Materials and Methods:A 3-year retrospective record based descriptive study with 254 neonates delivered at a tertiary care hospital in Coastal Karnataka, India was carried out.Results:The mean age of mothers was 28.57+/-4.3 years. Prematurity (39.3%) followed by hyperbilirubinemia (15.7%) and respiratory distress (12.2%) were the common complications seen, with a neonatal mortality rate of 2.3%. Antenatal complications (24.8%) and medical issues in the mother (13.7%) were the most common maternal risk factors associated with PROM. Although 59% cases delivered vaginally, Emergency Caesarean section was the mode of delivery in 97% of Caesarean cases. The median duration of latency was 590 minutes [interquartile (IQR) - 390-1,020 mins] with the highest median latency seen for 28-32 weeks of gestation which was 1,380 minutes (IQR: 672.5- 3,386.25 mins). Primiparity [Odds ratio (OR)- 1.99, 95% Confidence interval (CI)- 1.01-3.91, p=0.04] and preterm gestation (OR-2.12, 95% CI: 1.08-4.14, p=0.025) were factors associated with the increased latency period. A latency period >24 hours was found to be a significant factor associated with a poor Appearance, Pulse, Grimace, Activity and Respiration (APGAR) score (OR- 5.83, 95% CI- 2.85-11.93, p<0.001) and Neonatal Intensive Care Unit (NICU) admission (OR-5.98, 95% CI- 2.95-12.14, p<0.001).Conclusion:PROM is associated with a significant risk of neonatal morbidity and mortality with the most common complications being prematurity and low birth weight. Prolonged PROM increases the risk of neonatal complications. Early recognition and prompt management prevents the delay in intervention and also reduces the risk of neonatal complications.